In Situ Synthesis of Ternary Ni-Fe-Mo Nanosheet Arrays for OER in Water Electrolysis - Zhi Lu; Yifan Guo; Shilin Li; Jiaqi Ding; Yingzi Ren; Kun Tang; Jiefeng Wang; Chengxin Li; Zishuo Shi; Ziqi Sun; Hongbo Meng; Guangxin Wang (Molecules)
Water electrolysis is a promising path to the industrialization development of hydrogen energy. The exploitation of high-efficiency and inexpensive catalysts become important to the mass use of water decomposition. Ni-based nanomaterials have exhibited great potential for the catalysis of water splitting, which have attracted the attention of researchers around the world. Here, we prepared a novel Mo-doped NiFe-based layered double hydroxide (LDH) with a nanoarray microstructure on Ni foam. The doping amount of Mo can significantly change the microstructure of the electrocatalysis, which will further affect the oxygen evolution reaction (OER) performance of water splitting. This novel nanomaterial required only an overpotential of 227 mV for 10 mA cm−2 and a Tafel slope of 54.8 mV/dec in 1 M KOH. Meanwhile, there was no Mo, and the NiFe-LDH needed 233 mV to attain to 10 mA cm−2. Compared to the NiFe-LDH without Mo, the NiFeMo-LDH nanosheet arrays exhibited enhanced activities with 17.1 mV/dec less Tafel in OER. The good performance of the electrocatalyst is ascribed to the special nanosheet arrays and the heterostructure of the Ni-Fe-Mo system. These features help to increase the active surface, enhancing the efficient charge transfer and the reactive activity in OER.